2017
DOI: 10.3390/soils1010001
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Reactive Fe:S Ratios for Sulfur Impacts on Arsenic Uptake by Rice

Abstract: Human arsenic exposure from rice consumption is a global concern. Due to the vast areas of naturally contaminated soils in rice-producing regions, the only possibility for reducing hazardous exposure is to prevent As uptake and translocation to rice grain. Sulfur inhibits As mobility both in soil and plant, indicating that soil S content may be a primary factor controlling As uptake; indeed, gypsum (CaSO 4 ·H 2 O) has been proposed as a potential amendment. Here, we investigated S controls on rice As uptake wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…AsV also acts as a phosphate analogue with respect to transport across the root plasma membrane [86]. Pigna et al [87] reported that As toxicity in crops may be prevalent in situations where As pollution coexists with low available P. Sulphur (S) is an element that interacts toughly with As, particularly under reducing conditions; the reduced forms of S can make a binding with As(III) [88]. Srivastava et al [89] stated that S is important for plant growth as it regulates As tolerance over complexation of As by S-containing ligands (glutathione [GSH; γ-Glu-Cys-Gly] and PCs [GSH oligomers]).…”
Section: Concentration Of Nitrogen Phosphorous and Sulphate In Soilmentioning
confidence: 99%
“…AsV also acts as a phosphate analogue with respect to transport across the root plasma membrane [86]. Pigna et al [87] reported that As toxicity in crops may be prevalent in situations where As pollution coexists with low available P. Sulphur (S) is an element that interacts toughly with As, particularly under reducing conditions; the reduced forms of S can make a binding with As(III) [88]. Srivastava et al [89] stated that S is important for plant growth as it regulates As tolerance over complexation of As by S-containing ligands (glutathione [GSH; γ-Glu-Cys-Gly] and PCs [GSH oligomers]).…”
Section: Concentration Of Nitrogen Phosphorous and Sulphate In Soilmentioning
confidence: 99%
“…One driver for the occurrence of thiolation is sulfur (S) addition, even though naturally occurring S concentrations are already sufficient for As thiolation in paddy soils . Sulfur fertilization has recently been suggested to lower grain As concentration; however, no conclusive data have been obtained so far.…”
Section: Introductionmentioning
confidence: 99%
“…Thioarsenates are structural analogues to arsenate and form under sulfur-reducing conditions from arsenite by OH – /SH – -ligand exchange and oxidative addition of zerovalent sulfur. Sulfur-reducing conditions can occur in flooded rice paddy fields, , especially when sulfur (S) is applied as fertilizer. This has recently been suggested to lower grain As concentrations , with the beneficial side effect that emissions of methane are significantly decreased . No conclusive data about the effects of S fertilization have been obtained so far.…”
Section: Introductionmentioning
confidence: 99%